The gender gap in workplace authority in Sweden 1968 - 2000: A family affair? - Magnus Bygren; Michael Gähler (Institute for Labour Market Policy Evaluation (IFAU), 2007)
We assess whether the gender gap in authority in Sweden has changed during the period 1968–2000, and investigate to what extent family factors are responsible for this gap. We find that the gap has narrowed modestly during this period, and identify the life-event of parenthood as a major cause of the gap. When men become fathers, they gain authority; when women become mothers, they do not. Our fixed effects panel estimates of the effects of family factors deviate from the cross-sectional estimates, suggesting that unobserved individual heterogeneity – routinely neglected in this line of research – matters.
Keywords: J12; J13; J16; 330; Workplace authority; gender gap; work-family balance; Sweden; Arbeitsbeziehungen; Betriebsklima; Geschlecht; Familie-Beruf; Panel; Schweden